Analisis Dampak Overtime Kerja terhadap Kelelahan Fisik dan Mental Crew Kapal Mv. Manalagi Tisya - Wolfgang Alexander Defara; M. Imam Firdaus; Trisnowati Rahayu; Sutoyo Sutoyo (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study aims to analyze the impact of overtime work on physical and mental fatigue of the crew of the MV ship. Manalagi Tisya, by identifying the causal factors and consequences that may arise due to additional working hours. In this study, the researcher will apply a qualitative research method with a descriptive approach. This research was conducted by the author on the MV ship. Manalagi Tisya owned by PT Pelayaran Manalagi which is a subsidiary of PT Salam Pacific Indonesia Lines, with the ship call sign "YBTL2" and a total load capacity of 52201 MT. Data collection techniques in this study used observation, interviews and documentation. Data analysis techniques used data reduction, data presentation, drawing conclusions. Testing the validity of this research data used source triangulation, technical triangulation, and time triangulation. Based on the results of the study, it explains that the Overtime Pattern: The crew of the MV ship. Manalagi Tisya experienced an average of 4.5 hours of overtime per day, with the Engine Department experiencing the highest overtime (an average of 5.2 hours). Overtime most often occurs during loading and unloading at the port (35%) and when facing bad weather (27%), Physical Impact: Continuous overtime causes significant physical impacts in the form of sleep disturbances (80%), back and waist pain (70%), and muscle pain (60%), Mental Impact: As many as 85% of crew experience moderate to severe mental fatigue due to overtime, with the main symptoms being difficulty concentrating (75%), irritability (65%), and decreased decision-making ability (60%). Safety: There is a strong positive correlation (r = 0.82) between the duration of overtime and the frequency of safety incidents. The risk of incidents increases by 28% for every additional 2 hours of overtime, Work Performance: Overtime has an impact on decreased work performance, especially in problem-solving skills (45%), compliance with procedures (41%), and effective communication (37%), Overtime Management: The most effective overtime management strategies are task rotation and fatigue management training, but their implementation is still not optimal. Limited number of personnel and operational demands are the main obstacles in minimizing overtime, Regulatory Compliance: Average working hours of MV ship crew. Keywords: Overtime Work, Physical Fatigue, Mental Crew.